Electromagnetic Transients in Power Cables - da Silva, Filipe Faria; Leth Bak, Claus; SpringerLink (Online service) (London : Springer London : Imprint: Springer, 2013)
From the more basic concepts to the most advanced ones where long and laborious simulation models are required, Electromagnetic Transients in Power Cables provides a thorough insight into the study of electromagnetic transients and underground power cables. Explanations and demonstrations of different electromagnetic transient phenomena are provided, from simple lumped-parameter circuits to complex cable-based high voltage networks, as well as instructions on how to model the cables. Supported throughout by illustrations, circuit diagrams and simulation results, each chapter contains exercises, solutions and examples in order to develop a practical understanding of the topics. Harmonic analysis of cable-based networks and instructions on how to accurately model a cable-based network are also covered, including several (3z(Btricks(3y (Band workarounds to help less experienced engineers perform simulations and analyses more efficiently. Electromagnetic Transients in Power Cables is an invaluable resource for students and engineers new to the field, but also as a point of reference for more experienced industry professionals.s
1.Components Description -- 2.Simple Switching Transients -- 3.Travelling Waves -- 4.Transient Phenomena -- 5.System modelling and harmonics.
Keywords: Systems engineering; Production of electric energy or power; Energy; Energy Systems; Power Electronics, Electrical Machines and Networks; Circuits and Systems